ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN SYARIAH DENGAN PERBANKAN KONVENSIONAL (STUDI KASUS PADA BANK MUAMALAT SYARIAH DAN BANK TABUNGAN NEGARA) - SAIFUL MUNIR, MOCH. Saiful (Jurnal Akuntansi AKUNESA, 2013)
Bank is one institution that has an important role as institution supporting in theeconomy of a country, because serves as a media owner with between user funds.Good picture as bad a bank can be seen from its financial performance. Thebank's performance as a whole is an overview of achievements reached in thebank, both concerning the funds and operational, technology and humanresources. The study is done to compare financial performance between banksyariah with bank conventional public in the period 2008-2011 with ratio camel (capital, asset, management earnings, liquidity ).Keywords: the ratio of finance, bank financial performance, the ratio of theCAMEL